Pelatihan Pendirian Bank Sampah Kepada Masyarakat Perumahan Bukit Diponegoro RW 08 Kelurahan Tembalang, Kecamatan Tembalang, Kota Semarang - Atmanti, Hastarini Dwi; Wahyu Rejekiningsih, Tri; Anwaril Muttaqin, Aris; Majid, Rifaldi; Mukti Rinusara, Novita (LPPM ITB AAS Indonesia Surakarta, 2024)
The community service activity of the FEB UNDIP team carried out in RW 8 of Bukit Diponegoro Housing, Tembalang, Semarang aims to increase community participation in waste sorting activities and depositing them in the waste bank. Waste sorting and waste bank activities have not been carried out and established in the area. This community service activity is a form of Community Development Practice model. The Community Development Practice model applied in this community service activity aims to improve people's lives for the better.